Media sosial sebagai model tradisi bertandang baru di era digital - Andika Andika; Mulia Jaya (Universitas Muara Bungo, 2019)
The purpose of this research is to find out the use of Facebook as a model of a new visiting tradition in the digital era in Tunggul Bulin Village, Tabir Ilir District, Merangin District and to identify what factors influence the use of Facebook as a model of visiting tradition in the digital era. The method used in this study is a qualitative research method that is descriptive in nature. The method used in this study is a qualitative research method that is descriptive in nature. The informant selection technique used by researchers in this study is to use a purposive sampling method (sampling technique with certain considerations). The results of this study indicate that the tradition of travel gradually fades and disappears along with the development of knowledge, technology, art, and culture in the community, higher education in the community that makes the visiting tradition no longer carried out, they have sent messages, met at school, on the street, in the market, and in various places. Then also technology like media, electricity, and information also makes the tradition of travel fade and disappear, one of the biggest causes is the use of social media, especially Facebook. This is due to the use of Facebook in finding friends, getting to know from your facebook profile, communication without feeling nervous. AbstrakTujuan dilakukan penelitian ini adalah untuk mengetahui penggunaan facebook sebagai model tradisi bertandang baru di era digital di Desa Tunggul Bulin Kecamatan Tabir Ilir Kabupaten Merangin dan untuk mengidentifikasi apa faktor yang mempengaruhi penggunaan facebook sebagai model tradisi bertandang di era digital. Penelitian ini menggunakan pendekatan kualitatif dengan deskriptif. Hasil penelitian ini menunjukkan bahwa Tradisi bertandang lambat laun memudar dan menghilang seiring dengan perkembangan pengetahuan, teknologi, seni, dan budaya di tengah masyarakat, pendidikan yang tinggi di tengah masyarakat yang membuat tradisi bertandang tidak lagi dilakukan, mereka sudah berkirim pesan, bertemu di sekolah, di jalan, di pasar, dan di berbagai tempat. Kemudian juga teknologi seperti media, penerang listrik, dan informasi juga membuatkan tradisi bertandang memudar dan menghilang, salah satu penyebab terbesarnya adalah penggunaan media sosial, khususnya facebook. Hal ini dikarenakan penggunaan facebook dalam mencari teman, mengenal dari profil facebook, komunikasi tanpa rasa gugup.